Measuring and assessing motor skills of selected Croatian U12, U14 and U16 tennis players - Barbaros, Petar; Dudašek, Bernard; Milanović, Dragan; Šanjug, Sara; Galić, Marin (Frontiers in Physiology, 2023)
Purpose: The aim of this research is to analyse and to determine the differences between tennis players in younger age categories (U12, U14 and U16) in certain motor skills. Methods : A total of 60 tennis players ranked in the rankings of the Croatian Tennis Federation were measured by using 10 tests for assessing explosive strength in jump, speed, agility, and trunk strength. The tennis players were divided into three groups of 20 respondents. Statistically significant differences (p<0.05) between all age categories were found in indicators of frontal and lateral agility, running speed in the 11 20-meter shuttle run test, and explosive strength in jump and repetitive trunk strength. Results: Statistically significantly better results were shown between test subjects under 14 years compared to test subjects under 12 years in tests for the assessment of agility, in the 20 m sprint test, in tests of explosive strength of lower extremities and in the test of repetitive trunk strength. Subjects under 16 years achieved significantly better results compared to subjects under 14 years in tests for assessing agility, speed and explosiveness. Players under 16 years recorded significantly better results in all tests for assessing agility, speed, explosiveness of the lower extremities and in the test for assessing repetitive trunk strength. Statically significant differences were not detected in tests of running speed in the 5-meter and 10meter shuttle run tests among U12 and U14 tennis players, nor between U14 and U16 tennis players in the 60-second trunk flexion test. The highest heterogeneity of results in a single age category was determined in the test for assessing isometric trunk strength, and thus tennis players of different age categories do not differ significantly in this skill. Conclusion: The results of this research point to the development of specific motor skills in accordance with the increase of game demands and chronological age, however, also refer to the problem of muscle imbalance between front and back trunk musculature.